Combination of the 87Sr/86Sr ratio and light stable isotopic values (δ13C, δ15N and δD) for identifying the geographical origin of winter wheat in China. (1st December 2016) - Liu, Hongyan; Wei, Yimin; Lu, Hai; Wei, Shuai; Jiang, Tao; Zhang, Yingquan; Guo, Boli
Highlights: All parameters in wheat were significantly different among different regions. 87 Sr/ 86 Sr in soil extracts was significantly different among different regions. Positive correlation of 87 Sr/ 86 Sr was observed between wheat and soil extracts. 98.1% of correct classification rate was obtained using these four indicators. Abstract: This study aims to investigate whether isotopic signatures can be used to develop reliable fingerprints for discriminating the geographical origin of Chinese winter wheat, and to evaluate the discrimination effects of δ 13 C, δ 15 N and δD, alone or with 87 Sr/ 86 Sr. In this study, the values of δ 13 C, δ 15 N and δD, and the 87 Sr/ 86 Sr ratios of wheat and provenance soils from three regions were determined. Significant differences were found in all parameters of wheat and 87 Sr/ 86 Sr in soil extract (reflecting the bioavailable fraction of soil) among different regions. A significantly positive correlation was observed between the 87 Sr/ 86 Sr ratios of wheat and soil extracts. An overall correct classification rate of 77.8% was obtained for discriminating wheat from three regions based on light stable isotopes (δ 13 C, δ 15 N, and δD). The correct classification rate of 98.1% could be obtained with the combination of the 87 Sr/ 86 Sr ratio and the light stable isotopic values.